Navigating the AI frontier: European parliamentary insights on bias and regulation, preceding the AI Act - Allessia Chiappetta (Internet Policy Review, 2023)
Understanding Members of the European Parliament's (MEPs) attitudes and perceptions towards AI is crucial for aligning technological development with European values. This research paper focuses on the attitudes and perspectives of MEPs within the Special Committee on Artificial Intelligence in a Digital Age (AIDA) towards bias and discrimination in AI, as well as their views on regulatory measures. By conducting a critical discourse analysis of AIDA hearing transcripts, this study uncovers how MEPs perceive and comprehend bias and discrimination in AI and their stance on regulatory measures. The research argues that MEPs need to expand their understanding of AI due to their current limited comprehension. Findings reveal that MEPs view AI as both a risk and a source of innovation, with a prevailing sense of distrust. Some MEPs consider AI sentient and self- regulating, yet they all acknowledge the consequences of AI, including inherent biases and discriminatory practices - leading them to advocate for regulatory intervention. The insights gained from this study contribute to a deeper comprehension of the relationship between policymakers and emerging technologies, paving the way for informed decision-making and policy development within the European Union and beyond.
Keywords: 300; Artificial intelligence; Bias; Algorithmic discrimination; Technology; Regulation of innovation